2004
DOI: 10.1556/aagr.52.2004.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation regimes, mid-season drainage and time of application of nitrogen on growth and yield of hybrid rice

Abstract: Field experiments were conducted at the Central Farm of the Agricultural College and Research Institute, Madurai, India during the rabi (October-January) seasons of 1999-2000 and 2000-2001 in a split plot design with three replications. The soil of the experiments was sandy clay loam with a neutral reaction. The main plot consisted of six irrigation schedules with mid-season drainage, while four N splits were taken as sub- plots. The experimental results revealed that irrigation to a depth of 5 cm one day afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
6
1
0
Order By: Relevance
“…These results are in agreement with the findings of Chandrasekaran (1996) and Jayakumar and Krishnasamy (2005). Data in Table 2, also, revealed that growth attributes (number of days to 50 % heading, DM production, LAI and plant height) were significantly affected by combination between composted rice straw and NPK rates.…”
Section: -Growth Attributessupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in agreement with the findings of Chandrasekaran (1996) and Jayakumar and Krishnasamy (2005). Data in Table 2, also, revealed that growth attributes (number of days to 50 % heading, DM production, LAI and plant height) were significantly affected by combination between composted rice straw and NPK rates.…”
Section: -Growth Attributessupporting
confidence: 92%
“…One way for increasing water use efficiency, in rice growing, is alternating wet and dry irrigation (AWDI) method; viz., irrigation to submerge to a particular depth after disappearance of ponded water, in which rice fields are not kept continuously submerged, but, are allowed to dry, intermittently, during the rice growing stages. The beneficial effect of this irrigation practice was water saving and grain yield improvement in rice cultivars (Jayakumar and Krishnasamy, 2005). Intermittent irrigation regimes have been developed in some rice-production regions in attempts to reduce volumes of irrigation water and save water, where, Masian and Vijaykumar (1993) found that applying 5 cm of water at two days after disappearance of ponded water (DADPW) did not significantly reduce grain yield, but, it saved considerable water and had the highest water use efficiency, compared to continuous submergence.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen application at late growth stages delayed leaf aging and increased activity of root and the three active leaves during grain filling rate and reduced the sterility percentage which greatly increased grain yield. These results are in pertinence with those reported by Peng et al (1998), Edwin et al (2004), JayaKumar et al (2004, Mohammed (2006), Arafat (2007), El-Kallawy (2008) and Sathiya and Ramesh (2009).…”
Section: -8-grain Yield (T/ha)supporting
confidence: 90%
“…The heaviest 1000-grain weights (26.08 & 26.29 g) in the first and second seasons, respectively were produced with the sixth treatment T6 (1/4 as basal +1/4 at MT+1/4 at PI+ 1/4 at flowering) without significant differences with the fourth, third and second treatments (T4,T3 &T2).Whereas, the lightest 1000-grain weights (24.87 & 24.92 g) in 2011 and 2012 seasons, were obtained from the first treatment T1 (2/3 as basal +1/3 at panicle initiation) was applied without significant differences with the fifth treatment T5 ( 1/4 as basal + 1/4 at MT + 1/4 at BT + 1/4 at complete heading ). Similar trend was obtained by Surekha et al (1999), Jayakumar et al (2004) and El-Kallawy (2008).…”
Section: -7-1000-grain Weight (G)supporting
confidence: 90%
“…Increased grain yield by high rates of applied nitrogen may be due to the favorable growth with higher nutrient uptake, more translocation of carbohydrates towards the sink which increased yield attributes and resulted in producing higher grain yield [39]. Higher HI in younger seedlings might be due to the better crop growth, development and assimilates translocation to the grains, similar findings were reported by [25].…”
Section: Discussionsupporting
confidence: 74%